Effects of porcine jelly matrix (JMX) on gene expression of porcine umbilical cord (PUC) stem cells - Morton, Jodi Mirissa (Kansas State University, 2014)
Culturing stem cells is usually done on tissue-culture treated plastic. Over time the cells change their gene expression and start to differentiate. Porcine umbilical cord (PUC) stem cells express the embryonic transcription factors Oct4, Nanog and Sox2 and changes in their expression may be useful for to evaluating culture-induced changes in the cells. We developed an extract of porcine Wharton’s jelly matrix (JMX) that may provide some characteristics of the stem cell niche located in the umbilical cord. Our extract used whole cords and enzyme digestion to simplify preparation of the product. We compare cells cultured on plastic to those grown on thin and thick gels of JMX in four experiments. In Exp 1a and b, growing PUCs on a thick JMX coating for 3(1a) or 4(1b) d increased the number of cells at the end of culture (P < 0.05) with minimal effects on gene expression. In Exp 2 we compared PUCs grown on thin and thick layered JMX with added collagen (+C) and to control cells. The JMX layers caused the cells to adopt a small, round shape and to form clumps or colonies during culture. No differences (P > 0.10) were seen between thin10 +C and control wells for viable and total cell counts but thick layered +C resulted in decreased numbers of viable cells compared to thin + C (P < 0.10) and control wells (P < 0.05). In a follow up experiment (Exp. 3) growing the PUCs mixed within, rather than plating on top of, a thick layer of JMX + C caused marked morphological changes with dense 3-dimensional structures formed. Exp 4 compared JMX allowed to gel for 10 (Thin10 +C) or 60 (Thin60 +C) min before the non-gelled fraction was removed. There were no effects on cell numbers at the end of culture (P > 0.10) but Sox2 expression was increased in Thin60 +C compared to controls on plastic (P < 0.05) and Thin10 +C (P < 0.10). In summary, JMX extracts change cell morphology and in some formats increased cell proliferation and may increase Sox2 expression. Further investigation is needed to fully understand the effects of JMX on PUCs.
Keywords: Porcine Umbilical Cord Stem Cells; Porcine Jelly Matrix; Wharton's Jelly; Animal Sciences (0475)